A Novel Magnetic Resonance Imaging Score Predicts Neurodevelopmental Outcome After Perinatal Asphyxia and Therapeutic Hypothermia - Weeke, Lauren C.; Groenendaal, Floris; Mudigonda, Kalyani; Blennow, Mats; Lequin, Maarten H.; Meiners, Linda C.; van Haastert, Ingrid C.; Benders, Manon J.; Hallberg, Boubou; de Vries, Linda S. (The Journal of pediatrics, 2018)
To assess the predictive value of a novel magnetic resonance imaging (MRI) score, which includes diffusion-weighted imaging as well as assessment of the deep grey matter, white matter, and cerebellum, for neurodevelopmental outcome at 2 years and school age among term infants with hypoxic-ischemic encephalopathy treated with therapeutic hypothermia. This retrospective cohort study (cohort 1, The Netherlands 2008-2014; cohort 2, Sweden 2007-2012) including infants born at >36 weeks of gestational age treated with therapeutic hypothermia who had an MRI in the first weeks of life. The MRI score consisted of 3 subscores: deep grey matter, white matter/cortex, and cerebellum. Primary adverse outcome was defined as death, cerebral palsy, Bayley Scales of Infant and Toddler Development, third edition, motor or cognitive composite scores at 2 years of <85, or IQ at school age of <85. In cohort 1 (n = 97) and cohort 2 (n = 76) the grey matter subscore was an independent predictor of adverse outcome at 2 years (cohort 1, OR, 1.6; 95% CI, 1.3-1.9; cohort 2, OR, 1.4; 95% CI, 1.2-1.6), and school age (cohort 1, OR, 1.3; 95% CI, 1.2-1.5; cohort 2, OR, 1.3; 95% CI, 1.1-1.6). The white matter and cerebellum subscore did not add to the predictive value. The positive predictive value, negative predictive value, and area under the curve for the grey matter subscore were all >0.83 in both cohorts, whereas the specificity was >0.91 with variable sensitivity. A novel MRI score, which includes diffusion-weighted imaging and assesses all brain areas of importance in infants with therapeutic hypothermia after perinatal asphyxia, has predictive value for outcome at 2 years of age and at school age, for which the grey matter subscore can be used independently.